Case report: Peroral endoscopic myotomy for acute pandysautonomia-associated distal esophageal spasm in a child - Zhang, Hanhua; Chi, Biyun; Wang, Fengfan; Shao, Pei; Liu, Huanyu; Fang, Ying (Frontiers in Pediatrics, 2023)
Acute pandysautonomia-associated distal esophageal spasm is a rare disease with an unclear etiology. Here, we describe a 12-year-old boy with an acute pandysautonomia-associated distal esophageal spasm who was treated using a peroral endoscopic myotomy (POEM). The patient's clinical features included recurrent dysphagia, nausea, vomiting, growth retardation, and signs of autonomic nerve dysfunction (e.g., a decreased production of tears and sweat, and an increased production of saliva). Signs of the distal esophageal spasm were visible in upper gastrointestinal radiography, endoscopy, and high-resolution esophageal manometry. After the POEM, the patient exhibited improvements in nausea and vomiting, and his dysphagia symptoms were relieved by the 6-month follow-up visit. However, the patient's neurological problems persisted. The satisfactory short-term clinical responses in our patient suggest that POEM is feasible, safe, and effective for the treatment of acute pandysautonomia-associated distal esophageal spasms in children.